Diagnostic Yield and Outcomes of Computed Tomography of the Head in Critically Ill Nontrauma Patients. (November 2019) - Finkelmeier, Fabian; Walter, Sophie; Peiffer, Kai-Henrik; Cremer, Anjali; Tal, Andrea; Vogl, Thomas; Zeuzem, Stefan; Fichtlscherer, Stephan; Friedrich-Rust, Mireen; Bojunga, Jörg; Farnik, Harald
Background: Computed tomography of the head (HCT) is a widely used diagnostic tool, especially for emergency and trauma patients. However, the diagnostic yield and outcomes of HCT for patients on medical intensive care units (MICUs) are largely unknown. Methods: We retrospectively evaluated all head CTs from patients admitted to a single-center MICU during a 5-year period for CT indications, diagnostic yield, and therapeutic consequences. Uni- and multivariate analyses for the evaluation of risk factors for positive head CT were conducted. Results: Six hundred ninety (18.8%) of all patients during a 5-year period underwent HCT; 78.7% had negative CT results, while 21.3% of all patients had at least 1 new pathological finding. The main indication for acquiring CT scan of the head was an altered mental state (AMS) in 23.5%, followed by a new focal neurology in 20.7% and an inadequate wake up after stopping sedation in 14.9% of all patients. The most common new finding was intracerebral bleeding in 6.4%. In 6.7%, the CT scan itself led to a change of therapy of any kind. Admission after resuscitation or a new focal neurology were independent predictors of a positive CT. Psychic alteration and AMS were both independent predictors of a higher chance of a negative head CT. Positive HCT during MICU is an independent predictor of lower survival. Conclusions: New onset of focal neurologic deficit seems to be a good predictor for a positive CT, while AMS and psychic alterations seem to be very poor predictors. A positive head CT is an independent predictor of death for MICU patients.